1860 - választás és ünneplés a református egyházban - Szatmári Judit (2024)
The Protestant Patent published on September 1, 1859 served as a catalyst in the Hungarian Reformed Church. After the defeat of the revolution Haynau’s decree stripped the church of significant aspects of its autonomy, and in the first half of the decade it was forced to adapt to the situation. After rejecting the Entwurf, the draft of the new church constitution published by the imperial government in 1856, the Reformed Church returned to its old practices step by step. At the time of the publication of the Protestant Patent, religious and political discontent intertwined, and became a symbiotic movement. The Reformed Church was on the side of the Autonomists, those opposing the Patent, while its supporters, the Patentalists came from the Lutheran Church. The suspension of the Protestant Patent on May 15, 1860 didn’t have a significant impact on the elections of the Superintendents and Lay Presidents in the Reformed Church; the church districts returned to their practices from before 1848 without government authorization.
Keywords: Bölcsészettudományok; Történettudomány és régészet